Digital Twin and Physical Cyber Systems Applied to Ionizing Radiation: State of the Art in Metrology 4.0 (Brazilian Journal of Radiation Sciences (BJRS), 2024)
The Fourth Industrial Revolution has brought society many benefits, such as technological advances, and many challenges to be overcome. To increase the synergy between physical and digital systems, most often used in the optimization processes of physical systems, metrology 4.0 has become an essential tool for their development. A state-of-the-art paper is significant in understanding how these applications develop, focusing on Cyber-Physical Systems and Digital Twins in ionizing radiation. The online search was conducted in general and specific databases with keywords in English. Thus, twelve articles were analyzed and discussed, divided into three main themes: indirect applications, ionizing radiation metrology projects, and systematic reviews. It was possible to notice that the number of articles related to these technologies in ionizing radiation is still tiny compared to other areas, especially when compared to the industry, making it even more challenging.